Benefits of Robotic Process Automation in The Corporate Financial and Sales Functions, With Focus on The Credit Management Processes - Iulia Daniela POSTOLEA; Constanta-Nicoleta BODEA (Communications of International Proceedings, 2022)
In recent years, Robotic Process Automations (RPA) has been put under the spotlight and advertised as one of the best options to be considered when it to comes to reshaping future work implications in the operational areas of an organization. Future business perspectives must include automation and digitalization initiatives as well as RPA solutions when considering the technological progress applicable to their strategic plans. To this extent, the current paper will discuss the importance of credit management as part of the financial and sales processes and present a proposal for an automation solution, one that will be tracking receivables within a company. The proposed solution aims to facilitate information gathering as a basis in the decision-making processes and for much needed follow-up actions in connection with overdue receivables. The authors discuss these potential benefits resulting from such an implementation from the perspective of the whole cost saving efficiency process.
Keywords: Robotic Process Automation (RPA); credit management; cash flow; RPA benefits.